1986
DOI: 10.1103/physrevlett.57.543
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Isospin Mixing inHe4and Its Implications for Charge-Symmetry Breaking

Abstract: 7r-4 He inelastic cross sections have been measured at r ff =180 MeV. In the region of the J w = 1" states (£* -23 to 30 MeV) the 7r + /7r~ cross-section ratio R n was found to be 1.05 ±0.08 at ^lab^O 0 . Such a small deviation from 1.0 implies that isospin mixing between the T = 0 and T-\ states in 4 He is quite weak, in striking contrast to the strong isospin mixing deduced from the large ratio of photonucleon cross sections, R y = Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…A similar procedure was followed in Ref. [8], where RCCSM predictions for the pion inelastic scattering yields were successful in reproducing excitation energy spectra.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…A similar procedure was followed in Ref. [8], where RCCSM predictions for the pion inelastic scattering yields were successful in reproducing excitation energy spectra.…”
Section: Introductionmentioning
confidence: 95%
“…Such a large deviation from unity would have fundamental implications for the hadronic interaction, since it implies the existence of a charge symmetry-breaking (CSB) component of the internucleon force which, under standard assumptions, cannot be accounted for with the Coulomb interaction alone [1 -3]. However, work involving separate measurements of the cr(p, p), o(p, p), and tr(p, n) reactions, as well as 4He(e, e'N) and pion inelastic scattering studies call these results seriously into question [4][5][6][7][8] Pion inelastic scattering data have provided valuable information on the isospin character of the 4He continuum and have also provided tests of microscopic approaches to the four-body nuclear structure problem [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…-state telescopes at 60', 90'" and 120' to obtain simultaneous yields for the He(e, e' He)"and He(e, e' H)p reactions. In the only experiment to use real photons, Phillips et al [13] [14] as well as (p, p' H)/(p, p' He) reactions [15] both indicated no violation of charge symmetry, although the tr /tt ratio may be insensitive to isospin mixing due to nuclear structure eA'ects [16]. The inconsistency between the simultaneous ratio measurements …”
mentioning
confidence: 99%